滚子链传动横向振动稳定性分析 - 覃维献 (Jixie chuandong)
Based on the multi-body dynamics theory,the dynamic model of transverse vibration of roller chain drive system is established.Effects of the chain tension force and the rotational inertia of the link on transverse vibration of chain system are considered.On this basis,the natural characteristics of transverse vibration of roller chain drive system is studied by simulation example.Additionally,effects of the different boundary excitation conditions on the stability of transverse vibration of roller chain drive system are analyzed.The conclusions can provide guidance and reference to the dynamic analysis and design of mechanisms with roller chain drive systems.